Incidence of non-venereal lesions of the male genitalia: a study of 248 male cases at a tertiary care centre - P., Mamatha; Vardhan, Abhijeet; Arora, Sheena (International Journal of Research in Dermatology, 2020)
Background: Non-venereal dermatoses of external genitalia refers to those dermatoses involving external genitalia which are not sexually transmitted. These are associated with mental distress and guilt feelings in affected patients. The aim was to study the incidence of non-venereal lesions of the genitalia. Methods: This was a cross-sectional clinical observational study in 248 male patients attending dermatovenereology OPD of Vydehi Institute of Medical Sciences and Research Center with non-venereal genital lesions for a period of 18 months. Cases having venereal diseases were excluded from the study. Results: The study included 248 male patients with non-venereal genital lesions. A total of twenty-five different types of non-venereal dermatoses were noted in our study. The most common non-venereal dermatoses were Non-venereal infections, seen in 107 patients (43.14%), which includes scabies in 45 patients (18.14%), tinea cruris 25 patients (11.29%), candidiasis 28 (11.29%) followed by lichen simplex chronicus 23 cases (9.27%) and scrotal dermatitis (6.45%) other dermatoses include psoriasis, lichen planus, fixed drug eruptions, scrotal horn, histoid hansens, squamous cell carcinoma, Zoon’s balanitis. Conclusions: This study reflected the importance of diagnosis of non-Venereal dermatoses and refutes the general misconception that all genital lesions are of venereal origin.